VD_FINDINFO Jug / 2013 / 20 vom 30. November 2012 - VD Tribunal cantonal (2012)
ASSURANCE COLLECTIVE, ASSUREUR-MALADIE, DROIT À LA PRESTATION D'ASSURANCE, INDEMNITÉ JOURNALIÈRE | 33 LCA, 87 LCA, 404 CPC (CH)